How innovation really works - Knott, Anne Marie (McGraw-Hill Education, 2017)
Includes the 7 misconceptions about innovation trends and how to avoid the ones that dont work; this book shows you how to use Research Quotient to determine which R & D investments are most likely to drive growth to better utilize the innovation tools youre already using. --